PENGARUH TAX AVOIDANCE, EARNINGS MANAGEMENT, DAN KEPEMILIKAN MANAJERIAL TERHADAP COST OF DEBT - Dan Suminar; Luh Nadi (Jurnal Ilmiah Wahana Akuntansi, 2020)
This study aims to see and obtain empirical evidence regarding the effects of Tax Avoidance, Revenue Management and Managerial Ownership Against Debt Costs. This research was conducted at the manufacturing sector company consumer goods listed on the Indonesia Stock Exchange in 2014-2018. Population in this study were 51 companies listed on the Stock Exchange Indonesia se;ected using purposive sampling method, namely technique taking data sources with certain considerations. Data analysis method this research uses multiple linear regression analysis. Based on the research results show that Tax Avoidance has no effect on the Cost of Debt, Earning Management affects the Cost of Debt, and Managerial Ownership has no effect on the cost of accounts payable.